Pastoralism and Millet Cultivation During the Bronze Age in the Temperate Steppe Region of Northern China - Zhang, Yaping; Zhang, Ying; Hu, Songmei; Zhou, Xinying; Liu, Linjing; Liu, Junchi; Zhao, Keliang; Li, Xiaoqiang (Frontiers in Earth Science, 2021)
Abstract: Eastern and Western Asia were important centers for the domestication of plants and animals and they developed different agricultural practices and systems. The timing, routeway and mechanisms of the exchanges between the two centers have long been important scientific issues. The development of a mixed pastoral system (e.g., with the rearing of sheep, goats and cattle) and millet cultivation in the steppe region of northern China was the result of the link between the two cultures. However, little detailed information is available about the precise timing and mechanisms involved in this mixed of pastoralism and millet cultivation. To try to address the issue, we analyzed the pollen, fungal spores and phytolith contents of soil samples from the Bronze Age Zhukaigou site in the steppe area of North China, which was combined with AMS 14C dating of charcoal, millet and animal bones. A mixed pastoralism and millet agricultural system appeared at the site between 4000 and 3700 cal yr BP, and the intensity of animal husbandry increased in the later stage of occupation. Published data indicate that domestic sheep/goats appeared across a wide area of the steppe region of northern China after ~4000 cal yr BP. A comparison of records of sheep/goat rearing and paleoclimatic records from monsoon area in China leads us to conclude that the mixed of pastoralism and millet cultivation was promoted by the occurrence of drought events during 4200-4000 cal yr BP. Moreover, we suggest that mixed rainfed agriculture and animal husbandry increased the adaptability and resilience of the inhabitants of the region which enabled them to occupy the relatively arid environment of the monsoon marginal area of northern China.